THE EFFECTIVENESS OF SLOW DEEP BREATHING ON PAIN INTENSITY IN CHILDREN THROUGH CIRCUMSISION - Putu Arik Herliawati; Rezha Alivia Hildayanti; Ni Luh Seri Astuti (UNIVERSITAS AIRLANGGA, 2023)
Background: Circumcision is a surgical procedure that leaves scars and can be quite disturbing for children. This is because of the pain and limited movement that makes the child feel uncomfortable. The response to pain varies from child to child depending on the level of development or age of the child. Slow deep breathing is a conscious action to regulate deep and slow breathing which can have a relaxing effect. Relaxation therapy is widely used in everyday life to be able to overcome various problems such as stress, muscle tension, pain, respiratory problems, and others. Objective: The purpose of this study was to determine the effect of slow deep breathing complementary therapy on reducing pain intensity in children undergoing circumcision at the Marzuki Tabanan Foundation. Method : using pre-experimental method with one group pretest posttest design with purposive sampling technique. Results: From the results of the paired T-test, it was found that P value p: 0.013 <0.05, which means significant or there is an influence of Slow Deep Breathing therapy on pain intensity in children undergoing circumcision.